Lung fat embolism in cetaceans stranded in Canary islands - Méndez, Mariña; Arbelo Hernández, Manuel Antonio; Sierra Pulpillo, Eva María; Alves Godinho,Ana; Jáber Mohamad, José Raduán; Herráez Thomas, Pedro Manuel; Fernández Rodríguez, Antonio Jesús (2004)
The objective of this study was to evaluate the presence of fat emboli in lung tissues obtained from cetaceans stranded in Canary Islands. Lung samples from 84 cetaceans of 15 different species were studied. The animals stranded in Canary Islands coast between 1995 to 2003. The tissues had been fixed in 10% neutral buffered formaline solution. Tissues samples were prefijated with osmium tetroxide. Lately routin laboratorial technics for section and staining (hematoxilin-eosin) were made. 14 of 84 cetaceans of six different species, presented diverse lung fat embolism grades characterized by clear drops (H/E), black-stained with OsO4 in the lumen of small and medium size of pulmonary vessels: Kogia breviceps(4), Kogia simus(1), Mesoplodon densirostris (1), Physeter macrocephalus (3), Tursiops truncatus(1) y Ziphius cavirostris(4). All these animals belong to deep and long time diving species(13/14) excepting the one Tursiops truncatus. The cause of stranding and/or death of the 14 positive animals were relationed to: Antropogenic interactions (ship colision): 5/14; Massive strandings: 4/14; Unknown or natural causes: 5/14. According to these results, a clear association between lung fat emboli with violent trauma (ship colision) and with deep and long time diving species is observed.